Association between triglyceride to high-density lipoprotein cholesterol ratio and microalbuminuria in the Chinese population - Xue Zhang; Haofei Hu; Lishu He; Xia Huang; Zhichao Zhang; Lirong Tu; Heping Zhang; Feiyuan Liu; Xiaohui Liu; Yongcheng He (Scientific Reports)
Abstract The evidence for the association between the triglyceride (TG) to high-density lipoprotein cholesterol (HDL-c) ratio and the risk of developing microalbuminuria is still limited in the Chinese population. Therefore, our research will endeavor to explore the relationship between the two. The cross-sectional survey enrolled 32,877 general population from eight regional centers in China. If the urinary albumin-creatinine ratio (UACR) ≥ 30 mg/g, it was considered microalbuminuria. The dependent variable in the study was microalbuminuria, while the independent variable was the TG/HDL-c ratio. A binary logistic regression model was utilized to examine the independent association between the likelihood of microalbuminuria and the TG/HDL-c ratio. A generalized additive model (GAM) and spline smoothing were employed to investigate non-linear relationships between these two variables. To confirm the findings and pinpoint important turning points, subgroup and threshold effect tests were performed. The average age of the study participants was 57.67 ± 9.29 years, with 22,052 (67%) females and 10,825 (33%) males. The ratio of TG/HDL-c had a median value of 1.06, while the UACR had a median value of 9.92 mg/g. The prevalence of microalbuminuria was 14.4%. Following covariate adjustment, the prevalence of microalbuminuria and the TG/HDL-c ratio showed a significant positive connection (OR = 1.17,95% CI 1.13–1.21). Interestingly, we discovered a non-linear relationship between the occurrence of microalbuminuria and the TG/HDL-c ratio. At a TG/HDL-c ratio of 0.911, we detected an inflection point, with ORs of 1.12 (95% CI: 1.08, 1.17) on the right side of the point and 1.89 (95% CI: 1.51, 2.36) on the left. Subgroup analyses further validated the results. Our research revealed a positive and non-linear connection between the TG/HDL-c ratio and the prevalence of microalbumin in Chinese individuals. The connection was especially robust when the TG/HDL-c ratio was below 0.911. Reducing TG or raising HDL-c levels in order to lower the TG/HDL-c ratio may significantly mitigate the risk of microalbuminuria.